An approach to prepare nanosized HZSM-22 with enhanced lifetime in the methanol to hydrocarbon (MTH) reaction. Issue 108 (20th October 2015) - Wang, Jinbang; Xu, Shutao; Li, Jinzhe; Zhi, Yuchun; Zhang, Mozhi; He, Yanli; Wei, Yingxu; Guo, Xinwen; Liu, Zhongmin
Abstract : Nanosized HZSM-22 has been successfully prepared using ball milling combined with alkaline and acid post-treatment, and presented significant enhancement of catalytic stability due to the improvement of the diffusion effect. Abstract : Nanosized HZSM-22 has been successfully prepared using ball milling combined with alkaline and acid leaching treatment. The samples were characterized by XRD, XRF, nitrogen physical adsorption–desorption, SEM and solid state NMR. The results showed that the size of the zeolite crystal was greatly reduced after ball milling treatment, and that the crystallinity of the milled sample can be almost totally restored after further alkaline and acid treatment. The prepared nanosized HZSM-22 exhibited enhanced catalytic stability compared with the parent sample in the MTH reaction. Detailed product analysis implied that the improvement of the diffusion effect and the correspondingly reduced secondary reaction would be the most important factor for the long-term MTH operation over the nanosized catalyst.